Faktor Psikologis dan Intensitas Penggunaan Media Sosial Sebagai Prediktor Keputusan Pembelian pada Live Shopping TikTok - Wahyuni, Rika; Perdana Oskar, Dimas; Mariana, Rina; Irfani, Hadi; Theozard Fikri, Harry (Psyche 165 Journal, 2023)
The use of the internet as an online marketing medium which is classified as effective and reaches a large number of internet user communities. Market traffic has increased rapidly because purchasing decisions through online transactions are seen as providing convenience, one of which is using live shopping TikTok. Purchasing is an activity of buying products in the form of goods and services by customers through a complex thought process. The customer will assess and choose the best option. The purpose of the study was to determine whether there is a role for psychological factors and intensity using social media on purchasing decisions in live shopping TikTok. This research uses quantitative research methods. The subjects of this research were 85 housewives in Lubuk Begalung District Padang City selected using a random sampling technique. The data collection methods used are the intensity scale of psychological factors, scale of intensity using social media, and scale of purchasing decisions. Research data analyzed with multiple linear regression by the SPSS 26.0 for Windows. The results showed that: (1) psychological factors and Intensity using social media together on Purchasing decisions in live shopping TikTok with F value = 47,900, R2 = 0,734, dan p = 0,000; (2) there was significant impact of psychological factors on purchasing decisions in live shopping TikTok with beta coefficient = 0,206, t = 2,463and p value = 0,016; and (3) there was significant impact of intensity using social media on Purchasing decisions in live shopping TikTok with beta coefficient = 0,526, t = 6,968 and p value = 0,000. Contribution amounted to 73,4 percent.